Computer Assisted Counter System for Larvae and Juvenile Fish in Malaysian Fishing Hatcheries by Machine Learning Approach - Valliappan Raman; Sujata Navaratnam; Siti Fazilah; Sundresan A/L Perumal (Academy Publisher, 2024)
Non-Indexed Publication